Analisis Interaksi Sosial Antara Guru dan Siswa Melalui Pembelajaran Daring pada Siswa Kelas IV Sekolah Dasar - Monalisa, Maria Putri; Noviana, Eddy; Alpusari, Mahmud (Indonesian Research Journal on Education, 2022)
This study aims to determine the social contact and communication that occurs between teachers and students through online learning in class IV SDN 192 Pekanbaru. This type of research is descriptive qualitative research with a case study approach. The collection techniques used are observation and interviews, then the data is analyzed using the Miles and Huberman model. The number of subjects used in this study amounted to nine people. The results of this study indicate that the social interactions thatoccur between teachers and students in online learning are applied to three learning processes including: opening lesson, learning core and closing the lesson has been going well. This is known from social contact and communication. Social contact which consists of (1) conversation, (2) mutual understanding, and (3) cooperation. Meanwhile, communication consists of (1) openness, (2) empathy, (3) providing support and motivation, (4) positive feeling, (5) having similarities with others. Learning online does nothinder social interaction between teachers and students. The social interaction of teachers and students looks very familiar, the learning situation in the zoom application is very enthusiastic and there is a teacher's apperception for students.